2020
DOI: 10.3390/nu12061730
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dietary Behaviours during the COVID-19 Outbreak Confinement in the Spanish COVIDiet Study

Abstract: The aim of this study was to evaluate whether dietary behaviours of the Spanish adult population were changed during the COVID-19 outbreak confinement. For that purpose, an online questionnaire, based on 44 items including socio-demographic data, Mediterranean diet (MedDiet) Adherence Screener (MEDAS) as a reference of a healthy diet, processed foods intake, changes in their usual food choices and weight gain was distributed using social media and snowball sampling. A total of 7514 participants (37% aged below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

90
546
12
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(713 citation statements)
references
References 36 publications
90
546
12
27
Order By: Relevance
“…In detail, 8% of the Indians and 13% [ 14 ] and 36.8% [ 22 ] of the Italians reduced their daily intake by 25–50%. Similarly, the two Spanish surveys reported a 57.3% decrease in the weekly frequency of consumption in the longitudinal observation by Rodríguez-Pérez et al [ 18 ], and a 27% decrease in the cross-sectional evaluation carried out by Romeo-Arroyo et al [ 15 ].…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…In detail, 8% of the Indians and 13% [ 14 ] and 36.8% [ 22 ] of the Italians reduced their daily intake by 25–50%. Similarly, the two Spanish surveys reported a 57.3% decrease in the weekly frequency of consumption in the longitudinal observation by Rodríguez-Pérez et al [ 18 ], and a 27% decrease in the cross-sectional evaluation carried out by Romeo-Arroyo et al [ 15 ].…”
Section: Resultsmentioning
confidence: 75%
“…Changes in fat consumption were mainly assessed by recording the intake of dressing fats (olive oil, ghee, butter). It should be noted that although none of the cross-sectional studies reported this information, longitudinal observations showed a slight over-consumption, particularly referred to Indian [ 13 ] and Spanish populations [ 18 ]. In both these cases, the increased daily consumption as compared to the pre- COVID-19 era did not exceed 5%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unprecedented coronavirus disease (COVID-19) pandemic has created vast socioeconomic burdens [ 1 ], morbidity, and mortality [ 2 , 3 ]. The pandemic has also changed eating behaviors for the worse [ 4 , 5 , 6 , 7 ]. To deal with this challenge, the USA National Institute of Health Nutrition Research Task Force developed a 2020–2030 strategic plan to improve health and prevent or combat diseases and conditions that have been affected by food and nutrition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%